1986
DOI: 10.1073/pnas.83.2.470
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for rearrangement, amplification, and expression of c-myc in a human glioblastoma.

Abstract: Amplified cellular genes are frequently manifested in one of two cytologically recognizable forms, double minutes or homogeneously staining regions. Additionally, evidence is accumulating that aberrant expression of cellular genes (including oncogenes) may be mediated by gene amplification. We now describe the amplification and expression of the cellular oncogene c-myc in double-minute-containing cells from a patient with glioblastoma multiforme, and we have shown that the amplification is associated with rear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(64 citation statements)
references
References 26 publications
(24 reference statements)
5
59
0
Order By: Relevance
“…Expression of the proto-oncogene c-myc has been linked to the development of both undi erentiated and di erentiated glial cell tumors (Trent et al, 1986;LaRocca et al, 1989;MacGregor and Zi , 1990;Radner et al, 1993;Hirvonen et al, 1994;Chattopadhyay et al, 1995). Oligo-astrocytomas (mixed gliomas) are brain tumors composed of a mixture of astrocytes and oligodendrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the proto-oncogene c-myc has been linked to the development of both undi erentiated and di erentiated glial cell tumors (Trent et al, 1986;LaRocca et al, 1989;MacGregor and Zi , 1990;Radner et al, 1993;Hirvonen et al, 1994;Chattopadhyay et al, 1995). Oligo-astrocytomas (mixed gliomas) are brain tumors composed of a mixture of astrocytes and oligodendrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Most neuroectodermal tumors in the mature human brain are of astrocytic origin and in anaplastic variants, such as glioblastoma multiforme, overexpression of the cellular oncogene c-myc is common (Trent et al, 1986). The relatively low frequency of oligodendrocytic tumors indicates that oligodendrocytes are more resistant to neoplastic transformation than astrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Further suggestion of a role for Myc in regulating OPN gene transcription comes from prior studies with quail chondrocytes which indicated that constitutive expression of the v-myc oncogene increased OPN mRNA levels (Castagnola et al, 1991). Interestingly, several studies suggest that increased expression of Myc protein is a marker of the most malignant astrocytic tumors (Trent et al, 1986;Ehgelhard et al, 1989;Orian et al, 1992). This is likely due to ampli®cation of the myc gene, which is reported to occur in the highest grade of malignant astrocytoma (glioblastoma) (Trent et al, 1986;Ehgelhard et al, 1989;Orian et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies suggest that increased expression of Myc protein is a marker of the most malignant astrocytic tumors (Trent et al, 1986;Ehgelhard et al, 1989;Orian et al, 1992). This is likely due to ampli®cation of the myc gene, which is reported to occur in the highest grade of malignant astrocytoma (glioblastoma) (Trent et al, 1986;Ehgelhard et al, 1989;Orian et al, 1992). Furthermore, antisense oligonucleotides directed toward myc have been reported to signi®cantly inhibit the growth of malignant astrocytoma cells in vitro, suggesting a critical role for Myc in the proliferation of these tumors (Broaddus et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation